Ordered mesoporous materials for bioadsorption and biocatalysis - Hartmann, Martin (Chemistry of Materials, 2005)
The encapsulation of enzymes and other proteins into inorganic host materials has attracted considerable attention over the past few years. This research has demonstrated that biomolecules immobilized in inorganic matrixes retain their functional characteristics to a large extent. These new materials are of interest for applications as (optically based) biosensors and biocatalysts. We review the growing field of amino acids, vitamins, enzymes, and whole cells adsorbed (immobilized) onto ordered mesoporous silica and carbon molecular sieves. Strategies for the preparation of mesoporous supports and the essential properties of the resulting materials with respect to the envisaged applications are presented. Basic effects of the nature of the adsorption and various aspects of the application of these materials as biosensors, bicatalysts, and for drug release are discussed. Outlook of potential applications and further challenges are also provided. © 2005 American Chemical Society.